Need of Food Processing and Technology Management in India - Sharma, Swati; Vyas, Divya (Prabandhan: Indian Journal of Management, 2011)
Over the years, the profile of food processing sector has undergone a change. The product such as ready to eat (RTE), snack foods, breakfast cereals, extruded snack food and textural vegetables protein foods have shown tremendous growth during the last two decades. The food processing industries is a big earner of foreign exchange in India. There has been increase in process food industries in organized sector in recent times. In general, there has been an increase in demand and production of all the foods products including traditional convenience foods and snacks mixes. Several types of processed foods are available in the market. Big players from the world are pouring in the Indian market with varieties of products. At present, very few Indian industries are present in the market. Appropriate technology for the production of quality food products is still lagging. Thus, even Indian industrialists are using imported technology for processing various foods products. There are numerous types of foods taken in India. The processing technologies for Indian foods are in the pipeline and are slowly coming-up. Therefore, the scope of indigenous food processing industries is very high. Slowly, they will emerge and capture the market.